Geochemistry of the Ganesh Himal zinc-lead deposits, central Nepal Himalaya - Chakrabarti1, C. K.; Upret, B. N.; Ghosh, A. K. (Journal of Nepal Geological Society, 2004)
A dolomite hosted strata-bound high-grade (19-25%) zinc-lead sulphide deposit occurs, between 4,000 m and 5,100 m over an area of 5 km2 in the 7 km wide MCT zone of the Ganesh Himal area of central Nepal. The host crystalline milky white sugary dolomite occurs in a repeated sequence of garnet-mica schist, quartzite, calc-schist and concordant amphibolite of older Lesser Himalayan sequence (Upper Nawakot Group), all showing ductile deformation. The rocks along with the ore have undergone at least three phases of deformation. A series of overturned, steep northerly dipping and NE to ENE plunging anticlines and synclines form the dominating structure, characterised by disharmonic shape of the dolomite host rock because of apparent squeezing out from limbs into the axial regions. Compared to their strike lengths, the ore bodies and the host rock bodies have long extension along the plunge direction. The ore has a very simple composition of sphalerite-galena-pyrite with a little pyrrhotite, magnetite and chalcopyrite. Chemically, it consists mainly of zinc along with iron, lead, silver and very low silica, silicates and alumina. Concentrations of trace and rare elements are very low. Ore body types vary from dissemination and bands to massive sulphide lenses, arranged en echelon parallel to the schistosity/ bedding. The rocks of the area were subjected to almandine-amphibolite facies of metamorphism, to 750±150 MPa pressure and 500 °C to 750 °C temperature conditions. The latest thermal event was as young as 12 Ma. The lead isotope data are interpreted to establish an age of 875 to 785 Ma for the Ganesh Himal deposits, while sulphur isotope data imply an age greater than 650 Ma. The Ganesh Himal deposit appears to be Vindhyan equivalent in the Himalaya, showing highest metal values as on date. Only two out of six occurrences in the area have been explored so far. The ore reserve estimates stand at 2.4 million tonnes with 14.66% zinc, 3.01 % lead, and 23.5 g/t silver. Taking into account all the occurrences the Ganesh Himal basin might have had 861,000 tonnes zinc and 182,000 tonnes lead at the minimum. The lithologic sequence represents a shallow marine facies of deposition. The δ34 S values for Ganesh Himal sulphides indicate that the sulphur was probably produced by biogenic reduction of contemporaneous seawater sulphate. The lead isotope ratios of Ganesh Himal deposit fall on a single-stage growth curve, on which also fall many big deposits of the world, indicating that the Ganesh Himal zinc-lead deposit has high potential. The primary control of the mineralisation is stratigraphic, the present ore body configuration being controlled by south vergent folding related with the metamorphism and thrusting along the MCT. Pyrite framboids and geochemical characters of ore indicate that the mineralisation is syngenetic sedimentary, and it may have been deposited in association with a bioherm or reef in an anoxic environment. The source of metal ions is not clear yet, but the contemporaneous basic rock bodies providing the metal ions could be a possibility.